Study of Ni-V load acid-modified calcined kaolin (Mongolian Journal of Agricultural Sciences, 2015)
Kaolin as a natural clay mineral, is commercially available at low costs, which is of great importance. It has been demonstrated by existing research kaolin is a very effective carrier for photo catalyst, being able to promote the photocatalytic reaction process as well as improve the efficiency of reaction. The catalysts was characterized by FT-IR, XRD, UV-Vis spectra methods. Ni and V, amount of catalyst investigate. Simultaneously the effects of photocatalytic reaction activity about concentration of sulfuric acid, calcination temperature, ratio of Ni and V, amount of catalyst investigate. The experimental results show that the photocatalytic activity of calcined kaolin which is treated by 40% and loading Ni and V is significantly higher than other kaolin. The kaolin does not have the B acid and L acid peaks, but people could see the B acid and L acid peaks on the kaolin which is roasted and treated by sulfuric acid. In a certain range, the activity of the catalysts increase with the increasing of the concentration of acid.Journal of agricultural sciences №15 (02): 138-142, 2015